Optimasi Pertumbuhan dan Hasil Dua Varietas Bawang Merah Asal True Shallot Seed (TSS) Terhadap Aplikasi Pupuk NPK dan Magnesium - Jerry Maulana Siregar; Raja Aminuddin Siregar; Hilda Yanti Br. Torus Pane; Siti Yuli Meilanda Sormin; Risna Maya Sari (JURNAL AGROPLASMA, 2026)
The low productivity of shallots in Indonesia is mainly caused by the use of low-quality vegetative seeds and improper fertilization. The use of True Shallot Seed (TSS) combined with balanced NPK and magnesium fertilization is expected to increase shallot production. This study aimed to optimize the growth and yield of two TSS shallot varieties (Sanren F-1 and Lokananta) under various doses of NPK fertilizer (0, 83.3, 166.6, and 250 kg/ha) and magnesium fertilizer (0, 125, and 250 kg MgO/ha). The research was conducted from February to May 2021 at the experimental field of Universitas Muhammadiyah Sumatera Utara, Medan, at 25 meters above sea level. A factorial randomized complete block design with three factors and two replications was used. The results showed that the Sanren F-1 variety produced better number of leaves (7.0 leaves), number of bulbs per clump (2.7 bulbs), and fresh weight of bulbs per plot (812 g) compared to Lokananta, while the Lokananta variety produced larger bulb diameter (33.8 mm). Application of NPK fertilizer at 250 kg/ha significantly increased plant height, number of leaves, and harvest index. The combination of Sanren F-1 variety without magnesium and 250 kg NPK/ha produced the highest fresh weight of bulbs per plot (1027 g). The interaction between variety, NPK, and magnesium significantly affected all observed growth and yield parameters. The Sanren F-1 variety with 250 kg NPK/ha without magnesium is recommended to increase shallot productivity in lowlands. Keywords: lokananta, magnesium, NPK, sanren F-1, shallot, true shallot seed